2018
DOI: 10.18632/oncotarget.26137
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of pediatric glioblastoma cells promotes radioresistance and enhances glioma malignancyviagenome-wide transcriptome changes

Abstract: Pediatric glioblastoma (GBM) is a relatively rare brain tumor in children that has a dismal prognosis. Surgery followed by radiotherapy is the main treatment protocol used for older patients. The benefit of adjuvant chemotherapy is still limited due to a poor understanding of the underlying molecular and genetic changes that occur with irradiation of the tumor. In this study, we performed total RNA sequencing on an established stable radioresistant pediatric GBM cell line to identify mRNA expression changes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Secondly, the post-radiotherapy upregulation of genes controlling DNA repair, cell proliferation and anti-apoptosis is also believed to play an important role in radiotherapy-induced radioresistance, particularly when a sub-lethal dose of radiotherapy was cumulatively delivered [45]. This has been frequently reported by studies investigating adult glioblastomas and a very recent report has also confirmed the similar findings in pHGGs [46]. Last but not least, radiotherapy-induced generation and enrichment of cancer stem cells is also a major obstacle for maintaining the efficacy of radiotherapy to eradicate cancer cells.…”
Section: Role Of Hypoxia Hif Signaling Mediated Glucose Metabolism Asupporting
confidence: 55%
“…Secondly, the post-radiotherapy upregulation of genes controlling DNA repair, cell proliferation and anti-apoptosis is also believed to play an important role in radiotherapy-induced radioresistance, particularly when a sub-lethal dose of radiotherapy was cumulatively delivered [45]. This has been frequently reported by studies investigating adult glioblastomas and a very recent report has also confirmed the similar findings in pHGGs [46]. Last but not least, radiotherapy-induced generation and enrichment of cancer stem cells is also a major obstacle for maintaining the efficacy of radiotherapy to eradicate cancer cells.…”
Section: Role Of Hypoxia Hif Signaling Mediated Glucose Metabolism Asupporting
confidence: 55%
“…13 It is well documented that pathways induced tumor cell excessive proliferation and defective apoptosis account for the major mechanisms of radioresistance in cancer cells. [14][15][16] Therefore, here, we explored the roles of Hippo/YAP signaling in glioma cell proliferation and apoptosis under irradiation exposure. We report a new effective manner that downregulation of YAP can significantly enhance the radiosensitivity of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine was found to suppress proliferation of GB cell lines, and is associated with decreased activity of cathepsin B and up-regulation of tissue inhibitor of metalloproteinase-1 via the MAPK signaling pathway [86]. RNA sequencing of a radio-resistant pediatric GB cell line following radiation revealed the over-expression of pro-cathepsin B, implicating the potential for alternative therapies that target metalloproteinases or cathepsin B [87]. Expression of cathepsin B and cathepsin D was demonstrated in OCT4+ and SALL4+ CSCs in IDH-wildtype GB [88] (Figure 2).…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%